VIDEO ANIMASI 2D INFOGRAFIS APLIKASI LAKSA ( LAYANAN ASPIRASI KOTAK SARAN ANDA ) PADA DINAS KOMUNIKASI DAN INFORMASI (KOMINFO) PEMERINTAHAN KOTA TANGERANG - Lusyani Sunarya; Allyufi Fazril Rasyidin; Deka Witara (Journal Cerita: Creative Education of Research in Information Technology and Artificial Informatics, 2016)
he development of information and communication today is very important for the wider community. This is evidenced by the many pioneers of telecommunications and information which serves to realize the information and communication, either through print media such as newspapers, magazines, books, and electronic media such as radio, television, telephone, and internet. Currently the Department of Communication andInformation Technology, provide services or means of media information through some form of media in the form of social media and websites that in a sense is still not enough to meet the information needs effective services. In order to convey the latest information more effective services should at least have the means of media that can support the effectiveness of the communication process performed by an institution or agency. LAKSA application is a communication medium that serves to continue the public complaints that go through Call Center so that it can respond rapidly, so that people can easily give a message, complaints, suggestions, or report to the Office of Tangerang City Government. The methodology used in this study include problem analysis methods, data collection methods, methods of analysis of the design and method of production concept mavib (KPM) which includes: pre-production, production and post production. Thus in this research is intended to make the mediainfographic form of 2D animation, namely Design Video Animation Infographic Applications LAKSA (Report Aspiration Suggestion Box you) at the Department of Communications and Informatics of Tangerang, so that through the design of the media is expected to provide forms of information services more attractive, effective, and easily accepted, especially by the people of Tangerang.